2016
DOI: 10.1051/matecconf/20166706109
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Reliability of Metal Articles with Impulse Current Effect

Abstract: Investigation in duration effect of powerful electric current impulses on variation process of some properties of steels 40 and 45 and titanium alloy VT1-0 working in the high-cycle fatigue regimes was performed and nature of such an effect was detected in the research. By measuring the ultrasonic speed it was shown that electric current effect results in increase in reliability of articles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The effect achieved by the treatment cannot be associated with the heat effect as the registration and numerical modelling show a negligible temperature rise of about 2 o C which cannot promote any changes in the metal. The possible origin of the changes is via the non-thermal effect of the electric current and magnetic field as previously discussed in the literature [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]43]. Based on TEM observations as well as on measurements of microhardness and conductivity, it can be concluded that the treatment causes increased precipitation of GP-zones and leads to rearrangement of dislocations (see Figure 9).…”
Section: Effect Of Electric Current and Magnetic Field On Dislocations Rearrangement And Precipitationmentioning
confidence: 57%
See 2 more Smart Citations
“…The effect achieved by the treatment cannot be associated with the heat effect as the registration and numerical modelling show a negligible temperature rise of about 2 o C which cannot promote any changes in the metal. The possible origin of the changes is via the non-thermal effect of the electric current and magnetic field as previously discussed in the literature [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]43]. Based on TEM observations as well as on measurements of microhardness and conductivity, it can be concluded that the treatment causes increased precipitation of GP-zones and leads to rearrangement of dislocations (see Figure 9).…”
Section: Effect Of Electric Current and Magnetic Field On Dislocations Rearrangement And Precipitationmentioning
confidence: 57%
“…The development of new cost-effective techniques for fatigue resistance enhancement of metals is a challenge that is being addressed by both academic and industrial researchers. Among these techniques, the application of electropulsing [9][10][11][12][13][14][15][16][17][18][19][20] and the application of magnetic fields [21][22][23] are attracting attention, yet systematic investigations are still lacking. The similarity between these two treatments must be noted as a changing electric current in a conductive medium produces a magnetic field and vice versa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation